Poison most vial : a mystery - Carey, Benedict (New York : Amulet Books, 2012)
When a famous forensic scientist turns up dead and Ruby's father becomes the prime suspect. Ruby must marshal everyone she can to help solve the mystery and prove her father didn't poison his boss.
Keywords: Murder -- Fiction; Detective and mystery fiction